Suprasternal aortic arch echocardioscopy as a potential tool in detection and follow-up of mobile thrombi in patients with ischemic stroke - Esnaola Barriola, Inhar; Escriche Gorospe, Elena; Miguel Navas, Paula; Martínez Campos, Elisa; Molina Goicoechea, María; Capell Pascual, Ferran; Jiménez Delgado, Adrián; Muñoz Arrondo, Roberto (Frontiers in Neurology, 2025)
IntroductionSevere or complicated atheromatosis of the aortic arch represents an important and often underdiagnosed embolic source in patients with ischemic stroke. The presence of a floating thrombus has significant clinical relevance, as it is associated with a high risk of early recurrence. The aim of this study was to analyze the potential of echocardiographic examination through the suprasternal window in both the detection of embolic sources and the monitoring of the response to anticoagulant treatment in patients with mobile thrombi.MethodsThis case series study included ten consecutive patients with a mobile floating aortic arch thrombus associated with an atheromatous plaque, detected by focused echocardiography and confirmed by Computed Tomography Angiography (CTA). Epidemiological, clinical, radiological, and ultrasound characteristics were analyzed. Clinical and ultrasound follow-up was performed after initiation of anticoagulation as secondary prevention to assess the efficacy and safety of this treatment.ResultsTen patients (seven female) with a mean age of 76 years were identified. After anticoagulation, a complete resolution of the mobile thrombus was observed in eight of them during ultrasound follow-up. One patient suffered an ischemic recurrence. Two patients receiving associated antiplatelet therapy presented severe hemorrhagic complications, one of which was fatal. Once the disappearance of the mobile thrombus was detected, anticoagulation was discontinued, and no further ischemic recurrences were observed.DiscussionFloating thrombus of the aortic arch is an underdiagnosed but clinically relevant condition. The study of the aortic arch with echocardiography through the suprasternal window is a highly available and harmless technique, that may be highly useful for the detection and monitoring of response to treatment of this pathology. Furthermore, early anticoagulation could be an effective and safe treatment in these patients.